KOMPONEN-KOMPONEN KURIKULUM SEKOLAH MENENGAH PERTAMA - Muh Nasir, Tatang; Hasanah, Aan; ,, Hasbiyallah (Jurnal Inovatif Manajemen Pendidikan Islam, 2022)
Curriculum development is carried out through a contextual analysis process related to the internal and external challenges of education. This study aims to describe the components of the curriculum at SMPN 1 Kadipaten Tasikmalaya Regency. As for the focus of the study of the curriculum components, namely objectives, content/materials, implementation process, and curriculum evaluation. The research approach used is qualitative research with descriptive study methods. The results of this study indicate that the curriculum is very influential on the quality of the process and learning outcomes of students. This is viewed from various components of the curriculum, including; objectives, content, implementation process, and curriculum evaluation at SMPN 1 Kadipaten Tasikmalaya Regency. Through this research, it is concluded that the components of the curriculum function as a reference for learning and determine the direction of education.